Simon Bolivar rides again? Pathways toward integration between NAFTA, MERCOSUR, and the greater Andean region. - HINOJOSA-OJEDA, Raul A. (1997)
Presents the North American/South American Free Trade Area general equilibrium model which was developed to determine the economic impact of a variety of alternative scenarios for Western Hemispheric trade arrangements. Uses the model to compare a series of possible integration scenarios in the wake of the formation of NAFTA, MERCOSUR, and the Andean Pact, and analyses the economic policy problems related to these alternatives. Indicates that two types of trade relationships could be formed in the Western Hemsiphere : one is a competitive race among opposing blocs to build their own hub and spoke system; the other is a single complementary liberalization which is multilateralised across all blocs.